Challenges in the management of inflammatory bowel disease in sub-Saharan Africa. (October 2022) - Watermeyer, Gillian; Awuku, Yaw; Fredericks, Ernst; Epstein, David; Setshedi, Mashiko; Devani, Smita; Mudombi, Wisdom; Kassianides, Chris; Katsidzira, Leolin; ,
Summary: Inflammatory bowel disease (IBD) is generally considered a disease of high-income countries and is regarded as rare in sub-Saharan Africa. However, this assumption is almost certainly an underestimate, and the high burden of communicable diseases makes IBD in sub-Saharan Africa difficult to detect. Furthermore, some gastrointestinal infections can closely mimic IBD, contributing to delays in diagnosis and complicating therapeutic decision making. Constraints in endoscopic capacity alongside a scarcity of qualified diagnostic pathologists add to the difficulties. Implementing evidence-based guidelines recommended by international societies is challenging, mostly due to high costs and unavailability of medication. However, cost-effective approaches can still be implemented to manage IBD in sub-Saharan Africa as the predominant disease phenotype is mild-to-moderate ulcerative colitis, which often responds to treatment with basic medication. In this Series paper, we summarise the current management of IBD in sub-Saharan Africa and propose how it can be tailored to suit the epidemiological and socioeconomic specificities of the region. We also discuss measures required to address existing challenges, such as educating health-care workers about the diagnosis and management of IBD or improving endoscopic capacity.